Supporting Adolescent Newcomers in Literacy: The Impact of an After-School Literacy Program - Ahn, Sung Kyung; Jang, Luke (Language and Literacy / Langue et littératie, 2026)
School-aged newcomers have a pressing need for additional support to achieve their academic success. This article reports on the results of an after-school literacy program in Alberta, Canada, that aimed to support adolescent newcomers’ literacy. The primary data used include two high school students’ writing samples produced prior to and during the literacy program, and two tutors’ research notes. The study identifies the students’ learning needs and the impact of the literacy program on them. Findings inform instructional approaches and design promoting newcomer learners’ language and literacy development for school learning.